Release of transaminases subsequent to preservation in diluents . containing EDTA and cysteine HCL of beetal and cross bred (Beetal x Black bengal) buck spematozoa - SINGH, K H MANI; SINGH, M P; SINHA, A K (The Indian Journal of Animal Reproduction, 2007)
The study was conducted to observe the role of EDT A and Cysteine HCL on the semen of buckspermatozoa during preservation at refrigerator temperature. Egg Yolk citrate and Tris egg yolk fructose citric acidand yolk with EDTA and Cysteine HCL added@ 1 mg/ml in each extender separately were used for preservation.The leakage of transaminases (AST and ALT) from the spermatozoa at different hours of preservation in differentextenders was observed. Results obtained during the present study indicate that leakage of both AST and ALT enzymes was reduced by inclusion of Cysteine HCL and EDT A in both the diluents as compared to control (EYCand TEYFC) extender at all hours of preservation.
Keywords: Transaminases; Buck spermatozoa; ESTA; Cysteine; HCL